“I am Young, Why Should I Vaccinate?” How empathetic and aggressive communication on social media impact young adults’ attitudes toward COVID-19 vaccination - Kaňková, Jaroslava; Saumer, Melanie; Neureiter, Ariadne; Darovskikh, Sofia; Shargina, Elena; Matthes, Jörg (Frontiers in Public Health, 2023)
To combat the current COVID-19 pandemic, high vaccination rates are of crucial value. However, young people in particular tend to be hesitant toward vaccination. On social media, young adults are often called to vaccinate in an aggressive tone, arguing that there is no choice than to vaccinate and that all else is wrong. In an experimental study (N = 410), we investigated the effects of (a) empathetic vs. aggressive communication styles in social media postings and (b) the origin of the communicator on young adults' supportive attitudes toward COVID-19 vaccinations. We treated the gender of the communicator as a moderator, and expectancy violation, psychological distance as well as the perceived credibility of the communicator as mediators. Findings showed that an aggressive communication style generally had a negative impact on young adults' COVID-19 vaccination attitudes, fully mediated by expectancy violation and perceived credibility of the communicator. Gender and the origin of the communicator did not moderate this mediation processes. Further implications for online health communication strategies are discussed.